Establishing an organisational safety culture system in the Malaysian Mining Industry - Siti Noraishah, Ismail; Azizan, Ramli; Hanida, Abdul Aziz; Mohamad Aliasman, Morshidi; Muhammad Faizal, Zainal Abidin (Penerbit UMT, 2022)
Many industries have recognised safety culture as a mechanism to manage and reduce occupational accidents. Mutual understanding between management and employees is key to a successful organisational safety culture that prevents mining accidents. The mining industry in Malaysia has operated for almost 200 years. However, there is a lack of literature discussing the factors that contribute to organisational safety culture. Therefore, the objective of this study is to investigate the contributing factors to establishing an organisational safety culture system in the Malaysian mining industry. This qualitative study was conducted by interviewing ten respondents with extensive experience in the Malaysian mining industry. By applying thematic analysis, 10 organisational factors were identified: (1) Safety policy, (2) safety rules, (3) safety education, (4) safety program, (5) safety competency, (6) safety planning, (7) safety audit, (8) safety signage, (9) a competent SHO/leader, and (10) medical surveillance. In conclusion, safety policies, safety rules, and safety education are the three main factors needed to create an organisational safety culture in the Malaysian mining industry. This study was very helpful, especially to mine owners, mine operators, and enforcers as well as to mine employees, to improve their safety culture practices and reduce mining accidents or disasters in the future.